A práxis curricular da Educação Infantil nas pré-escolas públicas de Sorocaba à luz da articulação entre a Pedagogia Freireana e os pressupostos do Materialismo Histórico-dialético - Bravo, Daniela Gaete Sewaybricker (2024)
The present research has as its object of study the curricular praxis of Early Childhood Education in preschools in the municipal education network of Sorocaba in the light of the articulation between Freirean Pedagogy and the assumptions of Historical-dialectical Materialism and aims to analyze to what extent curricular praxis of preschools in the Sorocaba municipal education network come closer to or distance themselves from Freire's authentic curricular praxis in the light of Historical-dialectical Materialism. It presents a qualitative approach and makes use of bibliographical research, documentary analysis, observation of teaching practice and questionnaires with open and closed questions, which were applied in the second half of 2023 to management teams and educators of educational institutions in the municipal education network. Sorocaba-SP, with exclusive services for the pre-school stage. Thus, we used bibliographical research for the historical construction of the evolution of Brazilian Early Childhood Education and the constitution of preschools in the city of Sorocaba, in addition to characterizing the concept of praxis, classifying it within the context of Historical-dialectical Materialism, since Marx and Engels and its dissemination to Freire. We then present Freire's Liberating Education and his conception of curricular praxis, contemplating his conception of a critical-liberating curriculum and its consequences in Early Childhood Education. The analysis of the documents, the data collected via questionnaires, as well as the observation of the educators' performance in the classroom, were carried out using the Discursive Textual Analysis methodology, based on Freire's Authentic Curricular Praxis category, which is understood as inherent to the categories dialogue, problematization, awareness, which, in turn, are permeated by the concrete reality category. The subject praxiological parameters, contexts and processes were defined a priori, which helped us to size the curricular praxis of preschools in the municipal education network of Sorocaba. We conclude that, despite the efforts and good intentions expressed in the analysis of the questionnaires and the actions observed in the classroom, there is still a long way to go so that the curricular praxis in preschools in the municipal education network of Sorocaba becomes truly critical and liberating, closer to authentic praxis. However, we defend the viability of an authentic curricular praxis in Early Childhood Education, specifically for preschools in the municipal education network, and we propose the development of a critical-liberating curriculum, in addition to proposing a public policy of self(trans)formation permanent contact with teachers.